Water-soluble mercury ion sensing based on the thymine-Hg2+-thymine base pair using retroreflective Janus particle as an optical signaling probe - Chun, Hyeong Jin; Kim, Saemi; Han, Yong Duk; Kim, Dong Woo; Kim, Ka Ram; Kim, Hyo Sop; Kim, Jae Ho; Yoon, Hyun C. (Biosensors and Bioelectronics, 2018)
Herein, we report an optical sensing platform for mercury ions (Hg2+) in water based on the integration of Hg2+-mediated thymine-thymine (T-T) stabilization, a biotinylated stem-loop DNA probe, and a streptavidin-modified retroreflective Janus particle (SA-RJP). Two oligonucleotide probes, including a stem-loop DNA probe and an assistant DNA probe, were utilized. In the absence of Hg2+, the assistant DNA probe does not hybridize with the stem-loop probe due to their T-T mismatch, so the surface-immobilized stem-loop DNA probe remains a closed hairpin structure. In the presence of Hg2+, the DNA forms a double-stranded structure with the loop region via Hg2+-mediated T-T stabilization. This DNA hybridization induces stretching of the stem-loop DNA probe, exposing biotin. To translate these Hg2+-mediated structural changes in DNA probe into measurable signal, SA-RJP, an optical signaling label, is applied to recognize the exposed biotin. The number of biospecifically bound SA-RJPs is proportional to the concentration of Hg2+, so that the concentration of Hg2+ can be quantitatively analyzed by counting the number of RJPs. Using the system, a highly selective and sensitive measurement of Hg2+ was accomplished with a limit of detection of 0.027 nM. Considering the simplified optical instrumentation required for retroreflection-based RJP counting, RJP-assisted Hg2+ measurement can be accomplished in a much easier and inexpensive manner. Moreover, the detection of Hg2+ in real drinking water samples including tap and commercial bottled water was successfully carried out.
Keywords: DNA Probe; Janus particles; Mercury ion; Optical bio-sensors; Thymine base; Base Pairing; Biosensing Techniques; Drinking Water; Gold; Ions; Limit of Detection; Mercury; Nucleic Acid Hybridization; Oligonucleotide Probes; Thymine; Hg2+-mediated thymine- thymine base pairing; Mercury ion sensing; Optical biosensor; Retroreflective Janus particles; Stem-loop DNA probe